Applying joint traveltime and waveform inversion to image the Sichuan Basin, China. Issue 1 (1st August 2017) - Li, Ziang; Zhang, Jie
ABSTRACT: We apply a joint first‐arrival traveltime and early‐arrival waveform inversion method to image complex near‐surface structures in the Sichuan Basin, China. The area includes rugged topography and large near‐surface velocity variations. Due to the near‐surface effects, it is difficult to produce high‐quality reflection images of the deep subsurface. First‐arrival traveltime tomography is often applied for near‐surface imaging, but the results may not be sufficiently accurate because of ray assumptions and the limited traveltime information. Waveform inversion should allow complex structures to be resolved; however, it may fall into local minima because of cycle skipping issues and may also produce artefacts in very shallow areas that are associated with rugged topography. Therefore, we combine the advantages of the two methods and mitigate their problems by performing joint inversion of the two types of data. We demonstrate the effectiveness of the joint inversion method using synthetic and real data from Sichuan, China. In the real data example, we compare the velocity models resolved from waveform inversion alone with those resolved from the joint inversion. We calculate long‐wavelength static corrections and apply them to the data processing. The common midpoint stacking results show that the joint inversion method produces a more effective statics solution.